2015
DOI: 10.1590/1807-1929/agriambi.v19n2p126-133
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade e valor nutritivo do capim Tifton 85 irrigado e sobressemeado com aveia

Abstract: O trabalho foi conduzido no período de abril a novembro de 2012, em uma propriedade de produção leiteira, no município de Mariluz, Região Noroeste do Paraná, com o objetivo de avaliar a produtividade, a composição botânica e o valor nutritivo do capim Tifton 85 sobressemeado com aveia, na presença e ausência de irrigação. O delineamento experimental foi de blocos casualizados em parcelas sub-subdivididas, com 4 repetições. As parcelas foram sem e com irrigação. As subparcelas foram constituídas de sobressemead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
30
0
21

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 19 publications
6
30
0
21
Order By: Relevance
“…The productive increment in irrigated pastures, compared with rainfed cultivation, is evidenced by many authors (Müller et al, 2002;Gomes et al, 2015;Sanches et al, 2015). Research results have demonstrated the possibility of maintaining, in irrigated pastures during the dry period, 40 to 50% of the animal stocking rate that is maintained in the spring/summer, while these values comprehend only 10 to 20% in the absence of irrigation (Alvares, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The productive increment in irrigated pastures, compared with rainfed cultivation, is evidenced by many authors (Müller et al, 2002;Gomes et al, 2015;Sanches et al, 2015). Research results have demonstrated the possibility of maintaining, in irrigated pastures during the dry period, 40 to 50% of the animal stocking rate that is maintained in the spring/summer, while these values comprehend only 10 to 20% in the absence of irrigation (Alvares, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Nos ciclos seguintes a relação foi menor, próxima a 2, Sanches et al (2015) obtiveram valor médio de RFC 2,5 em pastagem de capim Tifton sobressemeada com aveia. A %MF foi maior em CC1, pois a presença do capim Marandu foi maior.…”
Section: P Souza Et Alunclassified
“…A maior produtividade e a mudança nos padrões fitotécnicos com a utilização da irrigação foram enfatizadas em diversos estudos (RIBEIRO et al, 2009;SANTOS et al, 2013b;SANCHES et al, 2015;ANTONIEL et al, 2016 …”
Section: Introductionunclassified
“…In recent years, the increasing use of technologies has allowed to increase productivity in cattle, which is dependent on techniques that improve the main food resource -pastures (SOARES et al, 2015). Also, in a climate that favors their growth, the key to ruminant production is in the diet from forages, being grazed or cultivated (MORRIS; KENYON, 2014;CHOBTANG et al, 2017aCHOBTANG et al, , 2017b.…”
Section: Introductionmentioning
confidence: 99%
“…Studies comparing the productivity of irrigated and nonirrigated pastures indicate increases in average daily accumulations between 25 and 55 kg ha -1 day -1 with irrigation (GOMES et al, 2015b;SANCHES et al, 2015SANCHES et al, , 2016SANCHES et al, , 2017DANTAS et al, 2016). Forage production throughout the year does not constantly meet animal requirements, and irrigation alone, despite mitigating, does not eliminate the seasonality of production (SANCHES et al, 2015). Thus, the consortium between summer and winter forages can optimize fodder production in the Hibernal period by extending the period of pasture utilization as well as improving its quality (SILVEIRA et al, 2015).…”
Section: Introductionmentioning
confidence: 99%